Waldvegetation in der Ostabdachung des Tibetischen Hochlands und die historische und gegenwärtige Entwaldung.: Das Beispiel Jiuzhaigous (Zitsa Degu; NNW-Sichuan) - Winkler, Daniel (ERDKUNDE, 1997)
The vast forests of Eastern Tibet are still insufficiently investigated, while they are being reduced at an alarming rate. Chinese figures point to 50% forest reduction in W-Sichuan in the last 40 years, mainly caused by a state-controlled forest industry. A massive extraction of timber is taking place, neglecting ecological and economical principles. Reforestation and sustainable forest management are still widely absent. Already in the past - extending over a period of millennia - substantial forest reduction was caused by man and his grazing animals. One of the main causes of Eastern Tibet’s widespread phenomenon of forest-free south-facing slopes seems to be pasturalism. Previously the absence of forests on the south-facing slopes had been attributed primarily to climatic conditions. However new research has shown that in Jiuzhaigou human impact is the primary cause for the absence of forests on the southern slopes. The forest vegetation of Eastern Tibet is presented by the example of Jiuzhaigou (Tibetan: Zitsa Degu). Jiuzhaigou Nature Reserve (103°46’-104°05’E / 32°55’-33°20’N) is located in NNW-Sichuan’s Min Shan mountains. The high mountain climate (744mm/a, annual mean temperature 7.3°C at 2400 m) is subtropically influenced and typical for the moister fringe of the eastern slope of the Plateau. The following altitudinal belts have been classified: 1. The montane mixed forest belt (2000-2700 m), which is differentiated into the lower montane belt (2000-2400 m), presently dominated by a pine-oak forest, here a hemlock mixed forest has barely survived; and the upper montane forest belt (2400-2700 m), dominated by fir-spruce mixed forests. 2. The altomontane cloud forest belt (2700-3500 m) consisting of the bamboo cloud forest belt (2700-3200 m), dominated by bamboo-fir-spruce forests, and the Rhododendron cloud forest belt (3200-3500 m) with spruce forests on the sunny slopes and fir forests on the shady slope; 3. The subalpine forest belt (3500-3800 m) consisting of fir stands on the shady slope and juniper stands on the sunny slope. Timberline is found at 3800 m altitude.